(untitled) (Revista Apotheke, 2023)
Starting from a constant experimentation and questioning about pictorial language, the transformation of a proposal over almost five decades of studio work is reported, going through realistic figuration, urban landscape, seascape, collage, the introduction of writing codes - letters, words, phrases - in painting, radical changes in support, and in format - rectangles and circles - as a research method, configuring the babelic construction in its paradigmatic realization.